2021
DOI: 10.1039/d1cc02896k
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic supramolecular architectures based on corannulene, fullerene, and beyond

Abstract: In this Feature Article, we survey the advances made in the field of fulleretic materials over the last five years. Merging the intriguing characteristics of fulleretic molecules with hierarchical materials...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 121 publications
0
5
0
Order By: Relevance
“…151 These buckybowls exhibit high affinity towards fullerenes through concave-convex p-p interactions when incorporated in tweezers architectures. 171,172 Sygula and coworkers provided the first strong evidence of supramolecular binding between a corannulene-based molecular tweezers and C 60 in solution and in the solid state. The authors found that this double concave host strongly binds to C 60 to form a stable complex (K a = 8600 M À1 in tolulene-d 8 ).…”
Section: Molecular Tweezers As Fullerene Hostsmentioning
confidence: 99%
See 1 more Smart Citation
“…151 These buckybowls exhibit high affinity towards fullerenes through concave-convex p-p interactions when incorporated in tweezers architectures. 171,172 Sygula and coworkers provided the first strong evidence of supramolecular binding between a corannulene-based molecular tweezers and C 60 in solution and in the solid state. The authors found that this double concave host strongly binds to C 60 to form a stable complex (K a = 8600 M À1 in tolulene-d 8 ).…”
Section: Molecular Tweezers As Fullerene Hostsmentioning
confidence: 99%
“…Fullerenes and their derivatives have emerged as valuable building blocks to construct functional carbon materials, which are widely used in different fields, such as sensors, liquid crystals, optoelectronics, catalysts, and energy conversion. 19,171,415,416 To obtain highly ordered fullerene 2D or 3D fullerene materials, numerous approaches have been developed. 417,418 While covalent cross-linking establishes robust 2D frameworks, the principles of supramolecular chemistry are vital for establishing order during synthesis and can be harnessed to generate 3D vdW (hetero)structures.…”
Section: D and 3d Assembliesmentioning
confidence: 99%
“…7,8 Besides, curved polycyclic aromatic compounds, as the fragment of fullerenes, have received more and more attention due to their unique properties which can be widely used in various fields such as lithium storage, 9 hydrogen storage and optoelectronic devices. [10][11][12] Sumanene, a typical representative of p-bowls with C 3V symmetry, was synthesized for the first time in 2003. 13 Since then, its derivatives have been found to have some special properties that enable them to be used as organic semiconductor materials such as charge transport materials.…”
Section: Introductionmentioning
confidence: 99%
“…Since corannulene was synthesized by Lawton and Barth from a multistep process in 1966, [ 1 ] it has become one of the most important molecular tool in material science and nanotechnological researches. [ 2 , 3 ] However, the challenges and difficulties involved in the synthetic method precluded the systematic investigation of this π ‐bowl molecule until a simpler preparation was developed by Scott and his co‐workers in early 1990s, [ 4 , 5 ] In 2012, Siegel’ s group discovered a kilogram‐scale synthesis of corannulene, [ 6 ] and accordingly, a variety of corannulene derivatives have been prepared and therefore available for studies in different disciplinary fields. [ 7 , 8 , 9 , 10 , 11 ] While a large number of corannulene‐based analogs have been reported, due to the extremely low solubility of most of the compounds under physiological conditions, there are very few examples that focus on the importance of this π ‐bowl molecule in pharmaceutical applications.…”
Section: Introductionmentioning
confidence: 99%